Dynamic model of sustainable development for a coffee supply chain - Faustino Lucas, Lesly Katterine (2023)
Peru is one of the world’s leading the production and exportation of organic coffee, so it is necessary to understand sustainable supply chain initiatives, which involve the 3 axes that encompass it (economic, social and environmental). In this line, the importance of risk factors in a supply chain process establishes sustainable objectives that is recognized. This research seeks to analyze and understand these factors and how they could impact the integration of sustainable development. For this, the methodology for modeling was System Dynamics. The results showed the importance of understanding these factors that impact a coffee supply chain. With this information, the sustainable conditions of production can be improved. It could be considered the most important factor in a coffee company. Complementary, two scenarios of possible variability of demand are presented, in a linear and exponential level, based on the analysis of historical data. Evaluating these scenarios, the linear equation was the best, because it is integrated, in a superior way, to initiating sustainable management in a coffee logistics chain.